Embryo reduction from the point of view of healthcare and ethics - Bompiani, A.; Guariglia, L.; Rosati, P. (Medicina e Morale, 1995)
The authors analyse the question of embryo "reduction" (ER ), that is, the elimination of embryos in multifetal pregnancies obtained following treatment for sterility, like drug induced ovulation or reproductive technologies. ER aims to obtain greater possibilities of survival up to delivery for the surviving fetuses. After illustrating ER from a medicai point of view, referring in particular to the clinical problems, the techniques used and the complications according to the most recent literature, the ethical and legal problems involved in ER are then dealt with. The following ethical points of view are classified: 1. the holiness or inviolability of life, which coincides with the teaching of the Catholic Magistero and is also shared outside the ecclesiastical field. This is the point of view shared by the authors of the article; 2. the point of view that only admits ER in order to prevent a very dangerous situation for the mother's health; 3. the utilitaristic vision that acknowledges prima facie duties and not absolute duties so that ER could be carried out even without certain maternal indication; 4. the woman's freedom of choice as the main ethical principle. After briefly rewieving the legal and deontological problems regarding ER, the possibilities of prevention are examined. ER is not to be considered a therapeutic attitude since it is contrary to the principle of the inviolability of Iife.